Modifications of aluminum film caused by micro-plasmoids and plasma spots in the effluent of an argon non-equilibrium plasma jet. (23rd August 2017) - Engelhardt, Max; Ries, Stefan; Hermanns, Patrick; Bibinov, Nikita; Awakowicz, Peter
Abstract: A smooth layer of hard aluminium film is deposited onto a glass substrate with a multi-frequency CCP discharge and then treated in the effluent of a non-equilibrium atmospheric pressure plasma jet (N-APPJ) operated with Ar flow. A thin filament is formed in the argon N-APPJ through contraction of a diffuse feather-like discharge. The aluminium surface treated in the effluents of the N-APPJ is significantly modified. Erosion tracks of different forms and micro-balls composed of aluminium are observed on the treated surface. Based on CCD images of active plasma discharge channels, SEM images of the treated surface and current–voltage characteristics, these surface modifications are interpreted as traces of plasma spots and plasmoids. Plasma spots are focused plasma channels, which are characterized by an intense emission in CCD images at the contact point of a plasma channel with the treated metal surface and by deep short tracks on the aluminium surface, observed in SEM images. Plasmoids are plasma objects without contact to any power supply which can produce long, thin and shallow traces, as can be observed on the treated surface using electron microscopy. Based on observed traces and numerous transformations of plasma spots to plasmoids and vice versa, it is supposed that both types of plasma objects are formed by an extremely high axial magnetic field and differ from each other due to the existence or absence of contact to a power supply and the consequential transport of electric current. The reason for the magnetic field at the axis of these plasma objects is possibly a circular current of electron pairs in vortices, which are formed in plasma by the interaction of ionization waves with the substrate surface. The extremely high magnetic field of plasma spots and plasmoids leads to a local destruction of the metal film and top layer of the glass substrate and to an attraction of paramagnetic materials, namely aluminium and oxygen. The magnetic attraction of aluminium is a reason for the extraction of some pieces of metal and the formation of erosion tracks and holes in the metal film. In the absence of metal atomization, the extracted aluminium forms spherical micro-particles, which are distributed over the surface of the treated metal film by the gas flow. A thin (100 nm) gold (diamagnetic) layer on top of the aluminium film surface reduces the erosion rate of plasma spots and plasmoids drastically (more than three orders of magnitude).